Problem-Based Learning Approach to Improve Writing Skills for Post Graduate Students - Nuurul Qadryanti; Fabiola D. Kurnia; Eka Fadilah (Budapest International Research and Critics University, 2022)
The purpose of this study was to examine the impact of Problem-Based Learning (PBL) on STKIP PGRI Sidoarjo's postgraduate students. The study used a pre-experimental design with a pretest-posttest design, with one group taking both the pretest and the posttest. Participants in the study were postgraduate students in their third semester (Batch 7) at STKIP PGRI Sidoarjo. The sample, on the other hand, was made up of 20 post-graduate students. The one-group pretest-posttest design allowed for only one intact group, which was chosen because the Problem-Based Learning (PBL) approach was appropriate for post-graduate writing students. This result indicated that the students' writing abilities had improved as a result of their involvement in the PBL. Furthermore, the SPSS Statistic 26 analysis reveals that the Sig. (2-tailed) value was. 002, which was lower than the Sig. level of 0.05, indicating that the null hypothesis was rejected. Based on the findings from the data examined, it is reasonable to conclude that incorporating Problem-Based Learning (PBL) as a learning approach has a significant impact and is effective on the writing skills of post-graduate students at STKIP PGRI Sidoarjo during pandemic Covid-19.